Uncertainties in measuring offshore gambling: A scoping review of Nordic approaches - Virve Marionneau; Søren Kristiansen; Tomi Roukka; Håkan Wall (PLoS ONE, 2026)
Background A part of online gambling consumption takes place in offshore markets. Lack of regulatory control over offshore offers erodes many public policy and public health objectives. Channelling consumption from offshore markets to regulated markets is therefore used as justification in many gambling policy decisions. Yet, it is currently unknown how reliable existing estimates of the size of offshore markets are. Methods This scoping review investigates how offshore gambling markets are measured in the Nordic context and what kinds of uncertainties are involved in existing measures. We searched available estimates of offshore gambling markets from academic and grey literature in four Nordic countries (Denmark, Finland, Norway, Sweden). The final sample consists of 32 reports. To supplement the results, we conducted key informant interviews and our own analysis of available data. Results 24 estimates concerned the monetary value of offshore gambling as a percentage of the full market. Nine estimates concerned the population prevalence of offshore gambling. In terms of methodologies, most studies reported figures from a private gambling intelligence company H2 gambling capital, either directly or combined with other data sources. Different methodological choices yielded different estimates. An important part of reports was funded by the gambling industry. Industry reports tended to have higher overall estimates of offshore gambling due to methodological choices. Conclusions The measurement of offshore gambling is a politically sensitive topic wrought with uncertainties. More reliable methods and figures are needed to better inform harm prevention and consumer protection in the online environment. Inaccurate offshore measures can be used as a tool for regulatory resistance. A transparent and scientifically validated measurement tool is needed to improve the evidence-base.